2021
DOI: 10.3390/cancers13102454
|View full text |Cite
|
Sign up to set email alerts
|

Unique Features of Hepatitis B Virus-Related Hepatocellular Carcinoma in Pathogenesis and Clinical Significance

Abstract: Hepatitis B virus (HBV) infection is one of the important risk factors for hepatocellular carcinoma (HCC) worldwide, accounting for around 50% of cases. Chronic hepatitis B infection generates an inflammatory microenvironment, in which hepatocytes undergoing repeated cycles of damage and regeneration accumulate genetic mutations predisposing them to cancer. A striking male dominance in HBV-related HCC highlights the influence of sex hormones which interact with viral factors to influence carcinogenesis. HBV is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 170 publications
(198 reference statements)
0
21
0
Order By: Relevance
“…Recently, it has also been suggested that alterations of hemostasis, particularly of platelets, could have a role in hepatocarcinogenesis [ 35 , 36 ]. Additional mechanisms that promote the induction of HCC in patients with HBV, HCV, and HBV-HDV infection are discussed below ( Table 1 ) [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Viral-related Hepatic Carcinogenesismentioning
confidence: 99%
“…Recently, it has also been suggested that alterations of hemostasis, particularly of platelets, could have a role in hepatocarcinogenesis [ 35 , 36 ]. Additional mechanisms that promote the induction of HCC in patients with HBV, HCV, and HBV-HDV infection are discussed below ( Table 1 ) [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Viral-related Hepatic Carcinogenesismentioning
confidence: 99%
“…The result suggests that hyperenhancement is significantly more common in HCC than IPT, which is consistent with previous report. Cirrhosis or diffuse parenchymal liver disease often results from chronic hepatitis infection, and HCC can develop under this kind of liver background (17)(18)(19). Whereas, IPT lesion is unlikely to be associated with certain liver background.…”
Section: Discussionmentioning
confidence: 99%
“…Significant biological processes, mainly cell replication control, mitochondrial functions, DNA repair, etc., are modulated by the expression of HBx [55]. Important signaling pathways involved in HCC, such as β-Catenin pathway [56], Src-dependent phosphatidylinositol-3 kinase pathway (PI3K/AKT) pathway [57], Ras-Rafmitogen activated protein kinase (MAPK) pathway [57], nuclear factor kappa B (NF-κB) pathway [58,59], Janus kinase/STAT (JAK/STAT) pathway [60] and protein kinase C (PKC) pathway, have all been reported to be aberrantly activated by HBx [61,62].…”
Section: Hbx Is a Multifunctional Viral Protein With Versatile Oncogenic Activitiesmentioning
confidence: 99%